Conceptualising Fan Persona - Kim Barbour; Mark Stewart (Persona Studies)
The entanglement of identity and performance within fandoms have been central components of fan studies, whether these fans are focused on sports, music, film, television, literature, celebrity, or something else. Their shared interest and investment in the fan object provide fans with common ground on which to build a collective identity, while the fan object can be a rich source of identity markers, from logos and colour schemes to moral values and philosophical positions. As argued by Busse and Gray in The Handbook of Media Audiences (2011, p. 426), being a member of a fandom facilitates “a particular identity that affects and shapes its members in ways beyond shared media consumption”. In this issue, we invited scholars to bring understandings of identity from fan studies into conversation with ideas of a strategic performance of self, extending existing work on fan personas from both within the Persona Studies journal and beyond. By doing so, we wished to explore how a ‘fan persona’ might be utilised by fans for specific purposes or in different interactions, or to frame individual perspectives, beliefs or interpretations within collective spaces.